PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA - Afrian, Nanda (Departemen Matematika, 2023)
One of the qualities that students need to learn is the capacity to solve mathematical problems. However, class XI MIPA SMA Pembangunan Laboratorium UNP students still have poor mathematical problem-solving skills. This is because the learning model used failed to develop students' math problem-solving abilities. The Think Talk Write (TTW) type of cooperative learning technique can be utilized to enhance students' math problem-solving skills. The Quasy Experiment and Nonequivalent Posttest-Only Control Group Design have been selected as the study design type and model, respectively. According to the research findings, pupils who use TTW are better at solving arithmetic problems than those who use direct learning techniques.Keywords. – Mathematical Problem-Solving Abilities, Cooperative Learning, Think Talk Write